TOY FRAGMENTS DISCOVERED IN NORTHERN VICUS OF RĂZBOIENI-CETATE (ALBA COUNTY) - George Bounegru; Rada Varga (Journal of Ancient History and Archaeology)
The current paper presents a few Roman toys discovered at Războieni-Cetate; more precisely, we are dealing with two Risi statuettes and fragments from three pull toys. The artefacts were found in civilian, presumably domestic, contexts in the northern part of the vicus and most probably are products of local officinae